DAMPAK LINGKUNGAN DAN RISIKO BENCANA PENGEMBANGAN DESA WISATA STUDI KASUS DI DESA WISATA SAMBI - Darmakusuma Darmanto, Sudarmadji (Jurnal Kawistara, 2014)
Merapivolcano has a lot of tourism potential objects. Local peopleâs traditions and the local panoramacaused many tourism villages to develope. Development of the tourismvillages in volcanic areas havepositive and negative impactsto the environment including to the local community. It also has somedisaster risks. This research was conducted at the Sambi Tourism Village located in the Southern Slopeof Merapi Volcano, to study the environmental impacts and disaster risks. The study was conductedby collecting primary and secondary data. Primary data collected by field observations and interviewswith local people and tourists. Data analyses was done by descriptive method. The results showedthat the Sambi Tourism Village has good tourism potential to be developed. Tourism developmenthas some positive impacts on economy of the local community, though there are some conflicts ofinterest among stakeholder. Negative impacts also occur, such as social tension and the degradation oflocal culture, especially âgotong royongâ.Sambi Tourism Village has some risk disaster due to MerapiVolcano activities, such as lahar floods and hot clouds.Environmental impacts and disaster risks shouldbe considered in the further development of Sambi Tourism Village